Representasi Tantangan Jurnalis Pada Film Dokumenter “Cyber Hell : Exposing An Internet Horror” (Analisis Semiotika Roland Barthes) - Sari, Sri Indah; Achiriah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Film is an audio-visual medium that can describe and convey messages, criticism, morals, norms, and others. Movies also have many types, one of which is a documentary film. Documentary films are films that retell reality events with more interesting and creative documentation, where this film is considered capable of influencing its audience. The movie that caught the researcher's attention was a documentary entitled Cyber Hell: Exposing an Internet Horror. Where this film is packaged in a storytelling style from the perspective of a journalist who plays a role in exposing sexual crimes that occur on telegram channels. This research focuses on each scene that contains challenges experienced by journalists when conducting investigative reporting. The purpose of this research is to provide knowledge about the real results of analysis through the methods used and describe the challenges experienced by journalists in conducting investigative reporting on cases of sexual exploitation and harassment through telegram channels. The research method used by the author is descriptive qualitative research method and Roland Barthes semiotic analysis technique. The data collection techniques used in this research are observation and documentation techniques. Researchers found that being a journalist is not easy, there are many challenges that must be overcome when carrying out tasks in this profession. The need for awareness of the challenges faced by journalists in today's social sphere is very important to ensure the quality of news published and reduce the risk of hatred, leaking of journalists' personal data, and the mental health of the journalists themselves.